2018
DOI: 10.3390/rs10050758
|View full text |Cite
|
Sign up to set email alerts
|

Metrology Assessment of the Accuracy of Precipitable Water Vapor Estimates from GPS Data Acquisition in Tropical Areas: The Tahiti Case

Abstract: High precision Global Positioning System (GPS) receivers, with the advantages of all-weather work and low cost, are now widely used to routinely monitor precipitable water (PW) vapor. They are so successful that the progressive phasing out of the costly and sparse in situ radio soundings (RS) is now a certainty. Nevertheless, the sub-daily to annual monitoring of high levels of the PW by GPS receivers in the tropics and the equatorial area still needs to be asserted in terms of metrology accuracy. This is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Furthermore, the correlation tends to decrease in summer and increase in winter [40]. The same authors include the seasonal and geographic dependence in the regression coefficients, as well as regional T m models [41][42][43][44][45][46][47][48]. An assessment of global and regional T m models can be seen in References [40,49].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the correlation tends to decrease in summer and increase in winter [40]. The same authors include the seasonal and geographic dependence in the regression coefficients, as well as regional T m models [41][42][43][44][45][46][47][48]. An assessment of global and regional T m models can be seen in References [40,49].…”
Section: Resultsmentioning
confidence: 99%
“…The mean slope of the volcanoes is around 8%, and the slopes of the flanks of the valleys can reach 40% to 70% [19] (Figure 1). The climate in Tahiti is very humid (meaning high PW values) [20] and characterized by dry (from May to October) and wet seasons (from November to April) that are governed by the South Pacific Convergence Zone (SPCZ) on the large scale and by the topography of a high volcanic island on the orographic scale [21]. The two GPS stations of this study are known in the IGS database as THTI and FAA1.…”
Section: Geomorphological and Climate Settingmentioning
confidence: 99%
“…Bevis et al (1992) [5] noted that to get the best results, the constants a and b should be "tuned" to specific areas and seasons. After the seminal work of Bevis et al, many additional efforts have been made to retrieve better GNSS PW estimates by developing better relationships, often based on regional and seasonal fits, between T m and T s (Bevis et al (1994) [35], Ross and Rosenfeld (1997) [37], Mendes et al (2000) [38], Wang et al (2005) [36], Suresh Raju et al (2007) [39], Yao et al (2012) [40], Huang et al (2018) [41] and [20]).…”
Section: The Estimation Of Gps Pw Valuesmentioning
confidence: 99%
“…Trent et al [6] observed the water vapor in the Planetary Boundary layer (PBL) using short-wave infrared observations from Japanese space agency (JAXA)'s Greenhouse Gases Observing SATellite (GOSAT); this is the first satellite single-sensor estimates of bulk PBL water vapor over land and (sunglint) ocean. Zhang et al [7] developed a new model to acquire the PWV estimates, using GPS observations in tropical areas. Du et al [8] proposed a unique approach to estimate the vapor pressure deficit using the AMSR-E and AMSR2 satellite observations.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Besides, remote sensing data enables global and regional hydrological applications, and water resources management, motivates new theories in mapping applications and offers new ways to predict and resolve global water resources conflicts. This Special Issue encompasses a number of contributions in satellite and airborne sensors applications in hydrology, including: mapping theories and applications, i.e., [1][2][3], new methods to better observe hydrological component, i.e., precipitation [4,5], precipitable water vapor (PWV) and vapor pressure deficit (VPD) [6][7][8], energy fluxes and evapotranspiration [9], and snowfall [10], and new methods to improve hydrological decision support system, i.e., [11]. The following section briefs the overall contributions in this Special Issue.…”
Section: Introductionmentioning
confidence: 99%